Qatar : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Qatar's report on the Observance of Standards and Codes for the Financial Action Task Force Recommendations for Anti-Money Laundering (AML) and Combating the Financing of Terrorism (CFT) is described. The two sectors that compose the financial system, the domestic sector and the Qatar Financial Center, are subject to different sets of preventive measures, which vary in depth and comprehensiveness. The allocation of resources to AML/CFT appears to be uneven, particularly in view of the rapid development and diversification of the economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Qatar